An effective compensating approach to the synthesis of sparse array with element-failures - Qin, Anqi; Sheng, Yijun (2019 International Applied Computational Electromagnetics Society Symposium - China (ACES), 2019)
The Covariance Matrix Adaptation Evolutionary Strategy (CMA-ES) Algorithm is used to compensate the failure of sparse array element. A fitness function is introduced to restrict the error between pre-failed pattern and measured pattern. To minimize the function we have introduced CMA-ES algorithm. Several numerical results demonstrate the ability of this array failure compensation algorithm.